PROSEDUR PENERBITAN SERTIFIKAT ELEKTRONIK SEBAGAI BUKTI AUTENTIK PENGUASAAN HAK ATAS TANAH: PROCEDURE FOR ISSUANCE OF ELECTRONIC CERTIFICATES AS AUTHENTIC EVIDENCE AUTHORIZATION OF LAND - Hakim, Arif Rahman; ALAY IDRUS, MUAMAR (Fakultas Hukum Universitas Gunung Rinjani, 2021)
That this thesis examines the juridical review of the procedure of issuing Electronic Certificates as authentic evidence of land rights mastery with the formulation of the problem, namely, how the land registration procedure to obtain an Electronic Certificate and how the power of Electronic certificates as authentic proof of land rights mastery. The purpose of this study was to find out and analyze how the procedure of issuing Electronic Certificates as authentic proof of land rights mastery. The benefits and usefulness of this research are theoretical benefits and practical benefits, using normative research methods. This research is normative research. By analyzing or reviewing a valid and competent Regulation to be used as a basis for problem-solving. The object of Sripsi's research is about the Procedure of issuing Electronic Seritifikat as authentic evidence of land rights mastery with several library reviews including a review of land rights, a review of land registration, a review of Certificates, then a review of Proof. While the source of legal materials used is divided into two, namely primary and secondary legal materials, in this thesis research the collection of legal materials by means of literature studies is by analyzing laws and regulations and is expected to be normative research. Based on the results of the study, the procedure of issuing Electronic Seritifikat should refer to Government Regulation No. 24 of 1997 concerning land registration for land that has not been registered and has not had physical and juridical evidence in accordance with articles 11 and 12. Then to get an Electronic Certificate or the change of analog certificate into an Electronic certificate refers to the Regulation of the Minister of Spatial Affairs of the head of the National Land Agency No. 1 of 2021 on Electronic Certificates, namely article 2, the next issued the implementing rules are government Regulation No. 18 of 2021 on management rights, land rights, flat units and land registration, namely article 84, Furthermore, the power of Electronic Certificates as authentic proof of land rights is included in the expansion of the letter proof tool, namely in article 1866 of the civil code and certificate of land rights can be canceled to its authenticity if it does not meet the elements of an authentic deed in accordance with the provisions of article 1868 of the civil code and further canceled if after 5 years of issuance of a Seritifkat there are those who feel objected can make a lawsuit to the office of the National Land Agency or to the court in accordance with article 32 paragraph (2) of Government Regulation No. 24 of 1997 concerning land registration.